The political economy of deforestation when distributional interests matter - a dynamic approach. (2016) - Sultan, Riad M.
Market and political forces are analysed in a two-sector political economy model as main determinants of deforestation and land conversion decisions. User groups involve in lobby and pressure activities to influence the decision maker to release land towards their specific sectors. The interaction is modelled as a cooperative bargaining process and the Nash solution corresponds to the political organisational equilibrium where the interests of all parties, including that of the decision maker are maximised. Using dynamic theory, the steady-state demand for forest land is derived, and the conclusion is that deforestation and land conversions are adjustment processes based on distributional interests, lobbying and the decision maker's self-interest motive, mainly to enhance the welfare of user groups.